In vitro knock‐out of miR‐155 suppresses leukemic and HCV virus loads in pediatric HCV‐4–associated acute lymphoid leukemia: A promising target therapy. Issue 4 (7th November 2019) - Hassan, Safaa S.; El‐Khazragy, Nashwa; Elshimy, Amal A.; Aboelhussein, Marwa M.; Saleh, Shereen A.; Fadel, Sayed; Atia, Hend A.; Matbouly, Safa; Tamer, Natalie
Abstract: Hepatitis C virus (HCV) infection is a major public health problem, having a high prevalence in Egypt. Leukemia and lymphoma have been associated with HCV infection. MicroRNA‐155 (miR‐155) has been reported to play a regulatory role in cancer, inflammation, and immune response to infection. The expression level of miR‐155 in HCV viremic patients is controversial; although high miR‐155 levels were demonstrated in HCV genotypes 1, 2, and 3, low levels of miR‐155 were detected in Egyptian patients with HCV genotype 4. Several studies have investigated the correlation between the levels of miRNA‐155 and the replication of HCV, others have evaluated miRNA‐155 as a prognostic biomarker in different types of cancer. No studies have investigated the impact of miRNA‐155 knockdown on HCV pediatric patients associated with childhood acute lymphoblastic leukemia (ALL). We knocked‐out the miR_155a in cultured polymorphonuclear cells (PBMCs) obtained from 60 children with ALL; 30 were associated with HCV‐4 infection and 30 were HCV negative. The miR_155a, HCV viral load, and cell proliferation werre assessed in treated and untreated cells using TaqMan assay quantitative polymerase chain reaction. We found that miRNA‐155 was significantly upregulated by seven folds in the HCV‐4 associated ALL group; while being linked to high HCV viral load and leukemic burden, miR_155a knock‐out can improve the disease outcome. We conclude that miR‐155 is a critical miRNA that is considered a therapeutic target in pediatric HCV leukemic patients. Abstract : Hepatitis C virus (HCV) infection is a major public health problem, having a high prevalence in Egypt. Leukemia and lymphoma have been associated with HCV infection. MicroRNA‐155 (miR‐155) has been reported to play a regulatory role in cancer, inflammation, and immune response to infectio. We conclude that miR‐155 is a critical miRNA that is considered a therapeutic target in pediatric HCV leukemic patients